Towards a mapping of the marginal : readings of art songs by Nigerian, Ghanaian, Egyptian and South African composers - Van Rhyn, Chris (Stellenbosch : Stellenbosch University, 2013)
Thesis (PhD)--Stellenbosch University, 2013.